2019
DOI: 10.1002/da.22983
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based psychotherapy trends among posttraumatic stress disorder patients in a national healthcare system, 2001–2014

Abstract: Background Although evidence‐based psychotherapies (EBPs) for posttraumatic stress disorder (PTSD) were implemented starting in 2005 in the veterans health administration (VHA), the largest national healthcare system in the U.S., the rate of initiation (uptake) and prevalence of these treatments in each calendar year have not been determined. We aimed to elucidate two metrics of EBP utilization, uptake and prevalence, following implementation. Methods Cohort study of Iraq and Afghanistan veterans in VHA (N = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…The current findings support that trauma-unrelated negative stimuli, rather than trauma stimuli, play an important role in PTSD remission. Though most effective therapies for PTSD are trauma-focused (Helpman et al, 2016;Hinton et al, 2009;Maguen et al, 2019;, nontrauma -focused interventions (such as Dialectical Behavioural Therapy, Yoga, and art therapy) are emerging (Racco & Vis, 2015). Kaczkurkin et al (2017) argued that because of the important role of maladaptive generalization in the pathological mechanism of PTSD, future psychotherapy may also involve trauma-like stimulation (generalized stimulation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current findings support that trauma-unrelated negative stimuli, rather than trauma stimuli, play an important role in PTSD remission. Though most effective therapies for PTSD are trauma-focused (Helpman et al, 2016;Hinton et al, 2009;Maguen et al, 2019;, nontrauma -focused interventions (such as Dialectical Behavioural Therapy, Yoga, and art therapy) are emerging (Racco & Vis, 2015). Kaczkurkin et al (2017) argued that because of the important role of maladaptive generalization in the pathological mechanism of PTSD, future psychotherapy may also involve trauma-like stimulation (generalized stimulation).…”
Section: Discussionmentioning
confidence: 99%
“…The current findings support that trauma‐unrelated negative stimuli, rather than trauma stimuli, play an important role in PTSD remission. Though most effective therapies for PTSD are trauma‐focused (Helpman et al., 2016 ; Hinton et al., 2009 ; Maguen et al., 2019 ; Mavranezouli, Megnin‐Viggars, et al., 2020 ; Mavranezouli, Megnin‐Viggars, et al., 2020 ), nontrauma ‐focused interventions (such as Dialectical Behavioural Therapy, Yoga, and art therapy) are emerging (Racco & Vis, 2015 ). Kaczkurkin et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of EBPs for PTSD is constrained by the number of providers who deliver these treatments (Borah et al, 2013, 2017). Challenges may arise when initial patient access to care is prioritized over availability of EBPs (Maguen, Holder, Madden, et al, 2020). Availability greatly affects wait times, which may reduce engagement; one study demonstrated that longer wait times from referral to intake and from referral to treatment were both associated with lower engagement in EBPs for PTSD (Possemato et al, 2018).…”
Section: Factors Influencing Referralmentioning
confidence: 99%
“…(van Rooij et al, 2016) However, the trauma-speci c component should be particularly meaningful in the PTSD-remittance mechanism because most effective therapies are trauma-focused, such as cognitive-behavioral therapy (CBT), (Hinton, Hofmann, Pollack, & Otto, 2009) eye movement desensitization and reprocessing (EMDR), (Mavranezouli et al, 2020) and prolonged exposure therapy (PE). (Helpman et al, 2016;Maguen et al, 2019) To study this critical component for remittance, traumarelated stimuli must be applied, and more trauma-speci c brain activity may be re ected in the contrast of trauma-related vs. unrelated conditions. However, no research used both conditions.…”
Section: Introductionmentioning
confidence: 99%